The status, aviculture and re-establishment of Brown Teal in New Zealand - Hayes, F Neil; Williams, Murray (Wildfowl, 1982)
Brown Teal Anas aucklandica chlorotis, New Zealand’s most threatened waterfowl, is restricted to a few relict populations, numbers no more than 1,500 and continues to decline slowly in both numbers and range. The species adapts readily to captivity and, in a co-operative programme involving Ducks Unlimited (NZ) and the New Zealand Wildlife Service, is being bred for release to establish new populations. Since 1977, 510 Teal have been reared in captivity and to date 390 have been released into the Manawatu district of North Island and on Matakana Island. Captive-reared birds have bred successfully in the wild.